In situ FTIR studies on mammalian cells. Issue 5 (2010) - Wolkers, Willem F.; Oldenhof, Harriëtte
Abstract : In this work, we describe the application of FTIR spectroscopy to study lipids and proteins, in cellular systems during heating and cooling. Various spectral analysis methods are described to simultaneously study membrane phase behavior and heat-induced protein denaturation in cells. Membrane phase behavior was studied by following the temperature dependence of the CH2 stretching vibration bands. Protein denaturation was studied using the amide-I and -III bands. Both amide-I and amide-III band analysis show that heat-induced denaturation of proteins within the cells is typically associated with an increase in extended β -sheet structures and a concomitant decrease in α-helical structures.